EFEK STATUS GIZI DAN FREKUENSI SENAM AEROBIK TERHADAP KADAR GULA DARAH PADA LANSIA PENDERITA DIABETES DI PUSKEMAS LUBUK BUAYA - Yusti Siana; Ade Teti Vani; Mhd Nurhuda; Vindi Domita (Nusantara Hasana Journal, 2023)
Background: DM sufferers need good and regular management to keep their blood sugar levels and nutritional status under control. One of the physical activities that can be done is aerobics. Objective: To determine the effect of aerobic exercise on nutritional status and blood sugar levels in elderly diabetics at the Lubuk Buaya Health Center. Methods: The scope of this research is the science of disease in the specialty of metabolism and geriatrics and nutrition. The research was conducted in December 2021. The type of research was Pre Experiment with a One-Group Pre Test-Post Test design. The affordable population in this study were elderly DM sufferers at the Lubuk Buaya Health Center with a total of 32 samples using simple random sampling technique. Univariate data analysis was presented in the form of frequency distribution and bivariate analysis using paired sample t-test and Wilcoxon signed ranks test, data processing using computerized SPSS program IBM version 25.0. Results: The most gender was female, namely 27 people (84.4%) and the most age were elderly (elderly), namely 16 people (50.0%), the most nutritional status before being given aerobics was overweight, namely 16 people (50.0 %) and the most nutritional status after being given aerobics was overweight, namely 15 people (46.9%), the average blood sugar level before being given aerobics was 219.16 with the lowest level being 144 and the highest level being 356, while the average level blood sugar after being given aerobic exercise, namely 203.38 with the lowest level being 139 and the highest level being 341, there was an effect of aerobic exercise on blood sugar levels in elderly diabetics at the Lubuk Buaya Health Center (p=0.000), and there was no effect of aerobic exercise on nutritional status in elderly diabetics at the Lubuk Buaya Health Center (p=0.686). Conclusion: The most gender is female and the most age is elderly (elderly), the most nutritional status before being given aerobics is overweight and the most nutritional status after being given aerobics is overweight, the average blood sugar level before being given aerobics is higher than average -the average blood sugar level after being given aerobic exercise, there is an effect of aerobic exercise on blood sugar levels in elderly diabetics at Lubuk Buaya Health Center, and there is no effect of aerobic exercise on nutritional status in elderly diabetics at Lubuk Buaya Health Center.